2011
DOI: 10.1017/s0031182011001235
|View full text |Cite
|
Sign up to set email alerts
|

Closing the praziquantel treatment gap: new steps in epidemiological monitoring and control of schistosomiasis in African infants and preschool-aged children

Abstract: SUMMARYWhere very young children come into contact with water containing schistosome cercariae, infections occur and schistosomiasis can be found. In high transmission environments, where mothers daily bathe their children with environmentally drawn water, many infants and preschool-aged children have schistosomiasis. This ‘new’ burden, inclusive of co-infections with Schistosoma haematobium and Schistosoma mansoni, is being formally explored as infected children are not presently targeted to receive praziquan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
123
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 48 publications
3
123
0
Order By: Relevance
“…Cases of reinfection were also observed in the study carried out by Stothard in Uganda, who found that even a 6-month period after two praziquantel administrations had little impact in decreasing prevalence. 16 Moreover, a slight increase in S. mansoni prevalence was observed between 2014 and 2015. A possible explanation is that the backwaters are the main source of water used by mothers to bathe their children, which is how they get infested in the first place.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cases of reinfection were also observed in the study carried out by Stothard in Uganda, who found that even a 6-month period after two praziquantel administrations had little impact in decreasing prevalence. 16 Moreover, a slight increase in S. mansoni prevalence was observed between 2014 and 2015. A possible explanation is that the backwaters are the main source of water used by mothers to bathe their children, which is how they get infested in the first place.…”
Section: Discussionmentioning
confidence: 97%
“…12 Our results are also in line with several studies showing that children under 2 years of age have active infection with this helminth. [16][17][18][19] Because of the efforts of the WHO authorities in Senegal, the medical regional authorities accepted to treat children under 6 years of age but only on an individual basis and under PNLB supervision in 2014. The study pointed out that these children were very difficult to treat and get reinfected very rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of pharmacological data and an appropriate formulation of praziquantel for pre-schoolers are important reasons why this age group is largely excluded from preventive chemotherapy. 25,26 However, pre-school-aged children might be particularly vulnerable to the negative consequences of an early-life infection with Schistosoma, because they would not get treatment until entering school. 27 Additionally, adolescents and adults are given far less attention than the school-aged population when it comes to schistosomiasis control.…”
Section: Discussionmentioning
confidence: 99%
“…18 Previous studies have highlighted such early Schistosoma infection in areas of high endemicity. 25,28,33,34 The negative health impact of such early infections has been emphasized. 31,32,35,36 Our observation of CCA detected in the urine of a child as young as 3 months in the absence of S. mansoni eggs in fecal samples is in line with recent observations from a study in Uganda using different approaches for detecting Schistosoma infections in pre-school-aged children.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinic setting, children are treated with two doses of 20 mg/kg PZQ at intervals ranging from 1 day to 4 weeks. Although pharmacokinetic studies are lacking, a suspension formulation or crushed tablets have been successfully used in the treatment of younger children [37,38]. Side effects may include nausea, emesis, diarrhea, dizziness, headache and pyrexia, but these are less likely to occur with the two-daily dosing regimen than with the single-dose treatment [38].…”
Section: Treatmentmentioning
confidence: 99%